Lower Free Triiodothyronine is a Risk Factor of Diabetic Peripheral Neuropathy in Patients with Type 2 Diabetes Mellitus - Chen Y; Sun L; Chen M; Zhang H; Song B; Wang H; Jiang A; Zhang L; Li S; Wang J; Wang W; Zhang H (Diabetes, Metabolic Syndrome and Obesity)
Yang Chen,1,* Lijie Sun,1,* Minghui Chen,1,* Hui Zhang,2 Bing Song,3 Hongxiao Wang,3 Aijun Jiang,1,4 Li Zhang,5 Sumei Li,1 Jumei Wang,1 Wei Wang,1 Haoqiang Zhang1 1Department of Endocrinology, Centre for Leading Medicine and Advanced Technologies of IHM, The First Affiliated Hospital of USTC, Division of Life Sciences and Medicine, University of Science and Technology of China, Hefei, People’s Republic of China; 2Henan Key Laboratory of Rare Diseases, Endocrinology and Metabolism Center, The First Affiliated Hospital, and College of Clinical Medicine of Henan University of Science and Technology, Luoyang, People’s Republic of China; 3Department of Endocrinology, The First Affiliated Hospital of Jinzhou Medical University, Jinzhou, People’s Republic of China; 4University of Science and Technology of China, Hefei, People’s Republic of China; 5ShuCheng People’s Hospital, Luan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wei Wang; Haoqiang Zhang, Email hfww2001@ustc.edu.cn; drhqzhang@ustc.edu.cnPurpose: Our objective is to investigate the potential involvement of free triiodothyronine (FT3), a key bioactive compound found in thyroid hormones (THs) in the pathogenesis of diabetic peripheral neuropathy (DPN) in patients diagnosed with type 2 diabetes mellitus (T2DM).Patients and Methods: A total of 121 T2DM patients were recruited. And then, they were divided into the control group and the DPN group. Clinical parameters were collected for each patient. Additionally, nerve conduction velocity was tested using neurophysiological methods. Correlation and regression analyses were employed to examine the relationship between the concentrations of FT3 and DPN.Results: Compared to 57 patients without DPN, 64 patients with DPN showed increased HbA1c and low-density lipoprotein cholesterol (LDL-C) levels (P=0.001 and 0.042), as well as decreased concentrations of FT3 (P=0.042). Additionally, FT3 levels are positively associated with the motor and sensory fibers conduction velocity of the Ulnar nerve, as well as the motor conduction velocity of the Tibial nerve, with (R=0.205, P=0.025; R=0.191, P=0.038; R=0.220, p=0.016) or without (R=0.257, P=0.004; R=0.227, P=0.012; R=0.227, p=0.012) adjustment for HbA1c and LDL-C. Furthermore, multiple linear regression analysis suggests that decreased FT3 levels may influence the motor and sensory fibers conduction velocity of the Ulnar nerve (β=0.795, P=0.025 and β=0.909, P=0.038), as well as the motor conduction velocity of the Tibial nerve (β=0.727, P=0.016). Moreover, our study demonstrated that decreased FT3 levels are one of the risk factors for DPN in T2DM patients, as determined by binary logistic regression analysis (OR=0.542, P=0.022).Conclusion: Lower concentrations of FT3 are one of the risk factors for DPN in patients with T2DM. Additionally, decreased FT3 levels may influence peripheral neuropathy, particularly affecting the motor and sensory fibers conduction velocity of the ulnar nerve, as well as the motor fiber conduction velocity of the tibial nerve.Keywords: free triiodothyronine, diabetic peripheral neuropathy, type 2 diabetes mellitus, thyroid hormone, conduction velocity of nerve